2021
DOI: 10.36740/wlek202107124
|View full text |Cite
|
Sign up to set email alerts
|

Functional Disordersof the Salivary Glands in Patients With Compression and Dislocation Dysfunction of the Temporomandibular Joint and Their Correction

Abstract: The aim: Is to assess the functional state of parotid glands and general secretion in patients with compression, dislocation dysfunction of TMJ, to correct the revealed disorders. Materials and methods: We examined 46 patients with dysfunction of TMJ. Examination included TMJ zonography and salivary glands sonography. We studied the general and parotid secretion, transparency, viscosity, pH of the oral fluid and the secretions of the parotid glands before and after treatment. The treatment of dysfunction and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Based on information from literary sources, it was found that women suffering from TMJ disorders consult a doctor more often, which was fully con rmed in our studies [11,12]. Despite the psychogenic theory of TMDs, some studies indicate that young women are more resistant to stress factors [13].…”
Section: Discussionsupporting
confidence: 79%
“…Based on information from literary sources, it was found that women suffering from TMJ disorders consult a doctor more often, which was fully con rmed in our studies [11,12]. Despite the psychogenic theory of TMDs, some studies indicate that young women are more resistant to stress factors [13].…”
Section: Discussionsupporting
confidence: 79%
“…This is due to the common vegetative innervation of the salivary glands and components of the TMJ. US is a dynamic exam, scanning different planes, therefore it may reveal a proximal enlarged parotid gland, or TMJ adjacent mass within the parotid gland presenting as a hypoechoic or heterogeneous US pattern, enabling further investigations to exclude possible tumor masses, such as pleomorphic adenoma of the parotid gland ( 106 , 107 ). Therefore, even if the physician is not particularly skilled at salivary gland US, he or she can anyhow quickly identify a suspicious lesion, as it presents with a different echogenicity compared to the surrounding tissue, addressing the patient to further analysis.…”
Section: Methodsmentioning
confidence: 99%